Analisis Efektivitas Penerapan Sistem Insentif Bagi Karyawan Di UD. Vita Jaya Meuble - Alfin Amal Chasani; Sintiya Tsalisa Agustina; Lailatul Magfiroh; Mochammad Isa Anshori (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This study aims to evaluate the effectiveness of implementing incentive systems for employees at UD. Vita Jaya Meuble. The research method used is descriptive qualitative analysis, involving surveys and interviews with the owners of the business as well as the company's management. Data were collected to assess to what extent the incentive system encourages employees to achieve company goals, improve productivity, and motivate performance. The results of the analysis will provide insights into the effectiveness of the existing incentive system and recommendations for possible improvements. This research is expected to contribute to improving employee performance and satisfaction, as well as operational efficiency at UD. Vita Jaya Meuble.